Pelatihan Pengolahan Limbah Garmen bagi Ibu Rumah Tangga Kelurahan Sukadanau - Putri Kamalia Hakim; Mansyur Srisudarso (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING ON GARMENT WASTE PROCESSING FOR HOUSEWIVES AT SUKADANAU VILLAGE. The purpose of this community service is to provide empowerment for housewives in Sukadanau sub-district, West Cikarang. The writers provided information on how to process garment waste into valuable hijab accessories through direct practice. In addition, they also thought procedures for creating marketplace accounts and how to sell and market the products through the marketplace. From the result of this community service, it can be concluded that this service received a good response. The participants in the end of the activity were able to make various forms of hijab brooches, necklaces and headdresses. Moreover, the participants also have accounts in several marketplaces as a means of marketing products.